Kurikulum Pendidikan Masa Penjajahan Jepang Di Sambas - Aslan Aslan (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2019)
Since Indonesia was colonized by the Dutch and Japanese, the development of Islamic educational institutions has shifted. During the Dutch period educational discrimination occurred, while in Japan the discrimination was abolished. However, everything colonialism that occurred in Indonesia caused deep wounds. This study aims to (1) describe the Japanese policy system towards Indonesia; and (2) describe the Japanese policy system for the Sambas people. The study was conducted with a literature study and to answer the focus of the study the analysis of the literature both books, national and international journals and other literature were considered supportive to answer the problem. The results of the study revealed; (1) Japan's policy system in Indonesia carries the vision of Nipponization taught in all fields, including in terms of education. Japan's aim is to be the leader of Greater Asia by influencing Indonesian society with an education system implemented by Japan. (2) the policy system in Sambas, Japan is more open to the Sambas people, because the key weakness of Sambas is religion. Japan is more open to opening Islamic organizations to get support as leaders of Greater Asia. In order for the mission of Japan to succeed, the educational institution eliminates discrimination by no longer looking at differences, which is the mission to instill the contents of Nipponization.